2013
DOI: 10.4236/ojmm.2013.33023
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Schistosomiasis in Children—Still a Concern in Part of the Ghanaian Capital City

Abstract: Schistosomiasis is a parasitic disease of the tropics which is estimated to affect up to 300 million people worldwide. While it is being successfully controlled in many countries, it remains a major public health problem, especially in developing countries including Ghana. Extensive work on schistosomiasis has been undertaken along the Volta River basin, leaving very little data and information on this infection in the urban and peri-urban areas in Ghana. This study was aimed at determining the urinary schisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The Zenu community is a "virgin" area in terms of schistosomiasis drug administration by the Neglected Tropical Disease Control Program. The prevalence of urinary schistosomiasis in this community has initially been reported as 30.7% [21].…”
Section: Design and Study Sitementioning
confidence: 95%
See 1 more Smart Citation
“…The Zenu community is a "virgin" area in terms of schistosomiasis drug administration by the Neglected Tropical Disease Control Program. The prevalence of urinary schistosomiasis in this community has initially been reported as 30.7% [21].…”
Section: Design and Study Sitementioning
confidence: 95%
“…Zenu is a small community situated specifically in the southern part of the Ashiaman municipality (a town on the outskirts of Tema) which is a suburb of Accra, the capital city of Ghana. Its geographical coordinates are 5 • 42'0" North, 0 • 20'0" West [21]. Subsistent farming and fishing remain the main economic activities, although a few inhabitants are civil servants ( Figure 1).…”
Section: Design and Study Sitementioning
confidence: 99%
“…Study conducted in Ghana, by Tetteh-Quarcoo, and collab., reported that the Prevalence of Schistosoma haematobium infection was 30.7 % [TETTEH- QUARCOO, et al, 2013] . Other study conducted in South Africa, reported that the Prevalence of Schistosoma haematobium infection was 73.2 % [MEENTS and BOYLES, 2010] .…”
Section: Risk Factors Associated With Schistosomiasis Infectionmentioning
confidence: 99%
“…Temperature, turbidity, pH Dengue [75] Temperature Malaria [59,75,87] E. coli, fecal coliform Cholera [45,61,62,81,88] E. coli, fecal coliform, turbidity, pH Dysentery [61,62,89] E. coli, fecal coliform Typhoid fever [61,62] E. coli, fecal coliform, BOD, temperature, DO Cryptosporidiosis [70,81] Fecal coliform Schistosomiasis [76,77,83,85,[90][91][92] E. coli, fecal coliform, temperature, turbidity Buruli ulcer [85] E. coli, fecal coliform, temperature, DO, BOD, TSS, turbidity Hookworm [92] pH = Potential of Hydrogen; DO = Dissolved Oxygen; BOD = Biochemical Oxygen Demand; TSS = Total Dissolved Solid.…”
Section: Water Quality Parameters Diseases Sourcesmentioning
confidence: 99%
“…Recreational activity was the major exposure and risk factor of schistosomiasis transmission Ghana [35,90] pH = Potential of Hydrogen; EC = Electro Conductivity; DO = Dissolved Oxygen; COD = Chemical Oxygen Demand; BOD = Biochemical Oxygen Demand.…”
Section: Choleramentioning
confidence: 99%